Metrics With Performance Indicators Used For Calculating the Mapping Strength of Course Outcome With Program Outcome - Yadav, Pradeep; Tomar, Archana; Soni, Rishi; Dubey, Gaurav; Bhargava, Chandra Prakash; Kumari, Jyoti (Journal of Engineering Education Transformations, 2025)
Outcome-Based Education (OBE) worldwide plays a pivotal role in enhancing academic standards by equipping students with problem-solving skills. To effectively assess the quality of education, it is essential to intricately map courses with specific program objectives (POs). The AICTE introduced a comprehensive exam reform policy in 2018, aiming to enhance assessment methodologies. This innovative approach involves categorizing each Program Outcome (PO) into distinct competencies and subsequently breaking down each competency into a specific number of performance indicators. This innovation enables a more nuanced evaluation of educational outcomes. In this context, a developed metric proves instrumental in aligning the data structure course with relevant performance indicators (PIs). This systematic mapping ensures that educational programs align with desired outcomes, fostering a dynamic and responsive learning environment conducive to addressing complex challenges.